2016
DOI: 10.3390/su8020195
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Social Values by 3D City Visualization in City Transformations

Abstract: Social sustainability is a widely used concept in urban planning research and practice. However, knowledge of spatial distributions of social values and aspects of social sustainability is required. Visualization of these distributions is also highly valuable, but challenging, and rarely attempted in sparsely populated urban environments in rural areas. This article presents a method that highlights social values in spatial models through 3D visualization, describes the methodology to generate the models, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Public policy in Sweden and elsewhere increasingly prescribe involvement of local communities in planning processes (Nilsson, 2010b). This is part of a general promotion of social, ecological and economic sustainability in urban planning (Hidman, 2018; Johansson et al , 2016; Nilsson, 2017). Studies of inclusive innovation and design highlight various approaches to broadened involvement in development processes, in regard to represented actors, applied perspectives and aspired outcomes (Heeks et al , 2014; Lindberg, 2018; Nyseth and Viken, 2009; Wikberg Nilsson and Jahnke, 2018).…”
Section: Co-creative Place Innovationmentioning
confidence: 99%
“…Public policy in Sweden and elsewhere increasingly prescribe involvement of local communities in planning processes (Nilsson, 2010b). This is part of a general promotion of social, ecological and economic sustainability in urban planning (Hidman, 2018; Johansson et al , 2016; Nilsson, 2017). Studies of inclusive innovation and design highlight various approaches to broadened involvement in development processes, in regard to represented actors, applied perspectives and aspired outcomes (Heeks et al , 2014; Lindberg, 2018; Nyseth and Viken, 2009; Wikberg Nilsson and Jahnke, 2018).…”
Section: Co-creative Place Innovationmentioning
confidence: 99%
“…Therefore, determining how to use existing land resources to improve development efficiency is particularly important. In practice, on the one hand, it is possible to adopt the method of adjusting the market structure, such as revitalizing urban stock land, and encouraging the development and utilization of urban underground space through three-dimensional development [53,54], multiple land use, and circulation utilization [33,55]. At the same time, the redevelopment of urban low-efficiency land should be actively supported, and the transformation of shantytowns, urban villages, and old factories should be accelerated [56,57].…”
Section: Conclusion and Policy Recommendationsmentioning
confidence: 99%
“…However, studies on sustainable developement mainly focus on the associations between this concern and environmental and/or economic issues (e.g. Johansson, Segerstedt & Jakobsson, 2016;Reed & Wilkinson, 2005;Yu, Tong, Tang, Yuan & Chen, 2018). Researchers have found that society has also had some interactions with other fields as environmental and/or economic changes have some influences on humans and vice versa (Cook & Esuna, 2014).…”
Section: Introductionmentioning
confidence: 99%